Hubungan Pengetahuan, Dukungan Suami, dan Jarak ke Fasilitas Kesehatan dengan Kepatuhan Jadwal Kunjungan Akseptor KB Depo Medroxy Progesterone Acetate (DMPA): Relationship between Knowledge, Husband's Support, and Distance to Health Facilities with Compliance with the Visit Schedule for KB Acceptors Depo Medroxy Progesterone Acetate (DMPA) - Olivia, Devi; Zakiah, Rofi’atun (Journal of Public Health Education, 2024)
Introduction: DMPA contraception is a contraceptive in the form of a liquid containing only the hormone progesterone which is injected intramuscularly into the woman's body (periodically) every 3 months. Knowledge, family support, and distance to health facilities are factors that influence adherence to the DMPA family planning visit schedule. Objectives: This study aims to determine the relationship between knowledge, husband's support, and distance to health facilities with adherence to DMPA injection family planning visits at PMB Yulis Setyaningsih, SKM., S.ST., Bd., M.Kes. Method: Using analytical descriptive methods with quantitative methods through a cross sectional approach. The sampling technique in this study used a total sampling technique with a sample of 42 respondents. The instrument used was a Likert scale questionnaire. Test data analysis using univariate analysis and bivariate analysis with chi-square test Result: The results showed that the relationship between knowledge compliance with visit compliance with p-value was 0.000, husband support for visit compliance with p-value was 0.005, and distance to health facilities on visit compliance with p-value was 0.00. Conclusion: This study concludes that there is a relationship between the variables of knowledge, husband's support, and distance to health facilities with adherence to DMPA injection family planning visits at PMB Yulis Setyaningsih, SKM., S.ST., Bd., M.Kes in 2022.